"Compensatory" uniparental disomy of chromosome 21 in two cases. Issue 7 (July 1994) - Bartsch, O; Petersen, M B; Stuhlmann, I; Mau, G; Frantzen, M; Schwinger, E; Antonarakis, S E; Mikkelsen, M
Abstract : Two cases of growth failure, microcephaly, facial dysmorphism, muscular hypertonia, and severe psychomotor retardation are described. At birth, both cases had cytogenetic mosaicism in lymphocytes and skin fibroblasts, in case 1 ring chromosome 21 and monosomy 21 and in case 2, deletion of chromosome 21 and monosomy 21. At a later age the lymphocyte karyotype changed almost completely to 46, XX, but the fibroblast karyotype remained as before. DNA polymorphism analysis described elsewhere indicated that the 46, XX lymphocytes contained two identical chromosomes 21 (isodisomy), in case 1 inherited from the father and in case 2 from the mother. The isodisomy was the result of duplication of a chromosome in mitosis after the loss of the homologous abnormal chromosome ("compensatory isodisomy"). We report here that this cytogenetic mechanism can result in false normal cytogenetic findings. The phenotypes were attributed to the cells with monosomy 21 in case 1 and to the deletion and monosomy of chromosome 21 in case 2.